"I always prefer to withdraw than use a condom": contextualising condomless sex among East Asian and sub-Saharan African international students in Sydney - Sylvester R. Okeke (BMC, 2022)
Abstract Background Incidence and prevalence of blood-borne viruses and sexually transmissible infections among young people continue to necessitate population-based studies to understand how contextualised sexual health services can be developed and implemented to promote protective behaviours such as consistent condom use. This study examined condomless sexual practice among a sample of East Asian and sub-Saharan African international university students in Sydney, Australia. Methods This qualitative study was methodologically guided by interpretative phenomenological analysis. Data was provided by 20 international students sampled from five universities in Sydney, who participated in either face-to-face or telephone semi-structured in-depth interviews. The interview sessions were audio-recorded, transcribed verbatim, coded in NVivo and analysed using reflexive thematic analysis. Results Condomless sexual practices appear to be common among the study group based on participants' self-reports of their own practices and the practices of friends and peers. Three themes contextualising condomless among the study participants were generated from the interview transcripts: (1) unanticipated sex, condom related stigma and alcohol use (2) pleasure-seeking, curiosity and intimacy (3) condomless sex as a gendered practice. Conclusions The result of this study has implications for public health research, practice and policy around design, implementation and evaluation of multi-layered and population-specific sexual health services that are tailored to addressing the needs of international students, who  migrate from traditional sexual cultures to Australia, where sexual norms are more liberal.